2009
DOI: 10.1590/s1517-83822009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Ocurrence of Staphylococcus aureus and multiplex pcr detection of classic enterotoxin genes in cheese and meat products

Abstract: Multiplex PCR was used to investigate the presence of enterotoxins genes (sea, seb, sec, sed and see) and femA gene (specific for Staphylococcus aureus) in coagulase-positive staphylococci (CPS) isolated from cheese and meat products. From 102 CPS isolates, 91 were positive for femA, 10 for sea, 12 for sed and four for see.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
6
30
1
6
Order By: Relevance
“…These results are consistent with the findings of Pelisser et al (2008) who identified 45.5% of S. aureus in 200 dairy and meat samples. Rall et al (2008) and Rosengren et al (2010) identified about 70% of strains as S. aureus in milk and fresh cheeses samples.…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with the findings of Pelisser et al (2008) who identified 45.5% of S. aureus in 200 dairy and meat samples. Rall et al (2008) and Rosengren et al (2010) identified about 70% of strains as S. aureus in milk and fresh cheeses samples.…”
Section: Resultssupporting
confidence: 92%
“…The rest of them consistently had a density higher than 4 log counts but none of these tested positive for enterotoxin. By investigation of mostly dairy products including cheeses, whey, butter, but also some samples from meat, meat products, sausages and eggs, S. aureus was detected in 13-20% of samples [16,17,20,52,53] or 35-45% [33,46] and even in 70-80% [42,54]. The prevalence of enterotoxigenic strains was higher than 30% in all mentioned studies.…”
Section: Source Of Contamination and Occurrence In The Environmentmentioning
confidence: 81%
“…According to references [34,45,46], the frequency of S. aureus occurrence varied from 6% to 28% in samples of raw milk. However, Rall et al [37] found that S. aureus was present in 70.4% of raw milk samples.…”
Section: Source Of Contamination and Occurrence In The Environmentmentioning
confidence: 99%
“…Forward and Reverse primers were selected from publications; forward 5-TGTATGTATGGAGGTGTAAC-3, Reverse 5-ATTAAC-CGAAGGTTCTGT-3. Primers were designed previously (31,32), and its detection power were optimized routinely. PCR product size is 270 bp.…”
Section: Methodsmentioning
confidence: 99%
“…Most strains of S. aureus are capable of producing enterotoxin. Staphylococcal enterotoxins are single-chain, low-molecular weight (27)(28)(29)(30)(31)(32)(33)(34) proteins. Although enterotoxins are mainly producedby some S. aureus strains, they might be produced by Staphylococcusintermedius, Staphylococcus hyicus, Staphylococcus xylosus, and Staphylococcus epidermidis.…”
Section: Introductionmentioning
confidence: 99%